ISIS governance : testing the theory of competitive control in Syria and Iraq - Paulsson, Henrik R. (2015)
In this study I examine ISIS's governance and population control methods through applying the theory of competitive control. By examining this ongoing case, this study adds to the growing body of literature through a systematic analysis of ISIS methods of population control and construction of identity. The time period studied in this dissertation starts with emergence of ISIS as a regional player in 2013 until January 2015, and focuses on its goals and methods. To achieve this goal, the theory of competitive control is applied to the case. The data used is from academic journals, newspaper and magazine articles, and published reports. I argue that the theory of competitive control explains the reasoning behind their methods of governance. I find that ISIS is using a wide-spectrum normative approach to its governance. This approach, which encompasses persuasive, administrative, and coercive methods for population control, strengthen the group and increases the level of support for ISIS, improving its standing in a conflict-ridden environment. It also argues that ISIS is constructing a new identity through the use of violence, polarizing communities even further. Aiming to be the defender of the Sunnis, it seeks to override traditional religious strains and implement its ideological imprint upon the population.